How does social trust affect corporate financial performance? The mediating role of corporate social responsibility. Issue 1 (6th September 2022) - Jung, Jae C.; Im, Junyon
Abstract: Prior studies assert that social trust may positively influence the economic performance of countries and firms (within those countries). This paper proposes a more nuanced mechanism whereby corporate social responsibility (CSR) mediates the relationship between country‐level social trust and firm‐level financial performance. Anchored in neo‐institutional theory, we theorize that social trust instills norms of trustworthiness and willingness to trust others guiding individual and corporate behaviors. In order to comply with such norms and gain legitimacy, firms in high‐trust society are more likely to commit to CSR activities that serve the interests of stakeholders. CSR activities, in turn, can positively influence financial performance by enabling firms to access stakeholders' resources and capabilities and to decrease transactions costs in the stakeholder relationships. We tested our theory by analyzing 9818 firm‐year observations across 34 countries, during the 2006 to 2015 period. Our analysis shows the expected CSR mediation in the relationship between social trust and firm‐level financial performance. Our findings are robust across different models addressing the concerns of endogeneity, alternative measures, and potential moderators.